2020
DOI: 10.1155/2020/2789410
|View full text |Cite
|
Sign up to set email alerts
|

Value of Plasma NGAL and Creatinine on First Day of Admission in the Diagnosis of Cardiorenal Syndrome Type 1

Abstract: Background. The presence of acute kidney injury in the setting of acute heart failure (AHF) or acute decompensated heart failure (ADHF) is a very common occurrence and was termed cardiorenal syndrome 1 (CRS1). Neutrophil gelatinase-associated lipocalin (NGAL) in the blood and urine is one of the earliest biomarkers of acute kidney injury due to ischemia or renal toxicity. This study was aimed to evaluate the diagnostic efficacy of plasma NGAL in the diagnosis of CRS1. Methods. There were 139 patients with AHF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The study of Dankova also proved elevated urine NGAL levels at admission to the hospital due to acute HF and predicted the following development of AKI [ 194 ]. Moreover, the report by Thai, which included 139 patients with acute heart failure, revealed that increased plasma NGAL concentrations along with elevated creatinine levels could predict the development of CRS 1 [ 195 ]. Since the rise in plasma NGAL exceeded an increase in serum creatinine, this also played a predictive role in the onset of acute kidney failure and thus allowed us to implement preventive therapeutic procedures [ 196 ].…”
Section: The Role Of Ngal In Cardiovascular Diseasesmentioning
confidence: 99%
“…The study of Dankova also proved elevated urine NGAL levels at admission to the hospital due to acute HF and predicted the following development of AKI [ 194 ]. Moreover, the report by Thai, which included 139 patients with acute heart failure, revealed that increased plasma NGAL concentrations along with elevated creatinine levels could predict the development of CRS 1 [ 195 ]. Since the rise in plasma NGAL exceeded an increase in serum creatinine, this also played a predictive role in the onset of acute kidney failure and thus allowed us to implement preventive therapeutic procedures [ 196 ].…”
Section: The Role Of Ngal In Cardiovascular Diseasesmentioning
confidence: 99%
“…Although previous data in post-cardiac surgery AKI supported this threshold [19], more recent studies in cirrhosis-associated AKI [20, 21] and paediatric AKI [15] have shown that the optimal uNGAL cut-off to discriminate ATN from a functional AKI could be lower. On the other hand, for pNGAL, some studies reported that the optimal cut-off value could be higher in some contexts [22]. Thus, tubular damage should perhaps be seen as a continuum in which NGAL, instead of being used in a dichotomous way based on a fixed “cut-off” threshold, should be considered as an additional tool to detect the presence or absence of potential structural damage, while considering the context of potential confounders such as severe CKD, inflammation, and concomitant infection.…”
Section: Discussionmentioning
confidence: 99%
“…MI-induced CRS in rats accelerates glomerular remodeling and the production of trace albuminuria (Dong et al, 2015). The predictive model combining plasma NGAL and creatinine D1 on the first day of admission had high accuracy in predicting CRS1 (Phan Thai et al, 2020). The combination of NGAL and NT proBNP in serum has early diagnostic value for type 1 CRS.…”
Section: Existing Biomarkers In Crsmentioning
confidence: 97%